Use of stripping column in methanol production technology based on synthesis gas - Rayimov, Zukhriddin Khayriddin ugli; Rajabov, Ghiyasiddin Alisher ugli (Science and Education, 2023)
It is today’s demand to organize and manage the production of products important for the national economy by reprocessing hydrocarbon raw materials based on modern technologies in the enterprises of the organic synthesis industry, as well as to constantly use the achievements of science and technology in practice. The production of chemical products, the development of enterprises is connected with the use of advanced technologies in them. Taking into account the above, the scientific article offers proposals for reducing the number of rectification columns used in the process of methanol production based on synthesis gas by using an evaporation section known as a stripping column.